The Coexistence of Colorectal Polyps in the Right Colon Increases the Malignant Risk of Laterally Spreading Tumors - Xiaonan Shen; Yao Zhang; Yunjia Zhao; Xiaobo Li; Zhizheng Ge; Hua Xiong; Danfeng Sun; Qinyan Gao; Yun Cui; Xiaoyu Chen; Yingxuan Chen; Jingyuan Fang (Gastroenterology Research and Practice)
Background. The coexistence of colorectal polyps with laterally spreading tumors (LSTs) is commonly observed during colonoscopy. However, there are rare studies that assess the malignant risks for LSTs with colorectal polyps, which might largely contribute to further strategies of treatment and follow-up plans in LSTs. Methods. We conducted a retrospective cohort study that enrolled 206 patients with LSTs in the Endoscopy Center and Endoscopy Research Institute, Renji Hospital, Shanghai Jiao Tong University, China. The subjects with LSTs were divided into two groups: the nonpolyp group with 89 patients and the polyp group with 117 patients. Binary logistic regression was used to identify the independent predictors of outcomes of interest. Results. The risk of the polyps’ coexistence phenomenon increased in males compared with females (OR=2.138, p=0.047), especially in those between 50 and 75 years old (OR=7.074, p=0.036). Tumor size (3–4 cm), LSTs with tubulovillous types, and history of polyps statistically increased the risk of the polyp coexistence phenomenon (OR=5.768, p=0.003; OR=36.345, p=0.024; OR=13.245, p<0.0001, respectively). LST-NG-PD (OR=20.982, p=0.017) and LSTs≥5 cm (OR=37.604, p=0.038) notably increased the malignant risk of LSTs. When the simultaneous polyps are located in the right colon, the risk of malignant LSTs (OR=58.540, p=0.013) positively increased. Conclusion. The simultaneous colorectal polyps in the right colon were the most important risk factor to predict the malignant risk of LSTs.